2017
DOI: 10.1039/c7cp00622e
|View full text |Cite
|
Sign up to set email alerts
|

Chiral segregation driven by a dynamical response of the adsorption footprint to the local adsorption environment: bitartrate on Cu(110)

Abstract: Local or global ordering of chiral molecules at a surface is a key step in both chiral separation and heterogeneous enantioselective catalysis. Using density functional theory and scanning probe microscopy results, we find that the accepted structural model for the well known bitartrate on Cu(110) chiral system cannot account for the chiral segregation observed. Instead, we show that this strongly bound, chiral adsorbate changes its adsorption footprint in response to the local environment. The flexible adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Molecules of life, such as proteins and sugars, come basically only in single handedness, meaning that their enantiomer does not appear. [8][9][10] At low coverage and after mild annealing, TA binds by deprotonation with both carboxylate end groups ("bitartrate") to the surface, but with increasing coverage, a transition to a single-carboxylate adsorbate mode ("mono-tartrate") was observed ( Figure 1). Examples are different action of chiral drugs and fragrances in the human body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules of life, such as proteins and sugars, come basically only in single handedness, meaning that their enantiomer does not appear. [8][9][10] At low coverage and after mild annealing, TA binds by deprotonation with both carboxylate end groups ("bitartrate") to the surface, but with increasing coverage, a transition to a single-carboxylate adsorbate mode ("mono-tartrate") was observed ( Figure 1). Examples are different action of chiral drugs and fragrances in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by Raval and co-workers performed with pure enantiomers revealed a transmission of molecular handedness into extended 2D domains, a coveragedependent polymorphism and two principle binding modes of the interaction of TA with the Cu(110) surface. [8][9][10] At low coverage and after mild annealing, TA binds by deprotonation with both carboxylate end groups ("bitartrate") to the surface, but with increasing coverage, a transition to a single-carboxylate adsorbate mode ("mono-tartrate") was observed ( Figure 1). For (R,S)-TA on Cu(110), it has been concluded that this diastereoisomer engages into similar adsorbate modes.…”
Section: Introductionmentioning
confidence: 99%
“…By recording STM images of low coverage regions, where aggregation into extended 2D structures is inhibited by the finite diffusion length, we are also able to identify isolated bitartrate trimers on the Cu(110) terraces, as shown in Figure 1 c. The appearance of isolated trimers, in preference to individual bitartrate molecules, indicates that the trimer is the thermodynamically stable unit, consistent with DFT structure calculations that find the trimer is held together by intermolecular H-bonds, with weak dispersion and through-surface interactions assembling the trimers into rows to form the 2D structure. 24 …”
Section: Resultsmentioning
confidence: 99%
“… 23 The bitartrate is strongly bound to Cu by two bidentate carboxylate ligands and ordered into linear structures by weak intermolecular hydrogen bonds, with a bare metal channel separating neighboring bitartrate rows. 24 We show that water initially decorates the metal channels, forming strong hydrogen bonds to the polar O ligands exposed along the edge of the bitartrate rows. Further adsorption forms water clusters along the exposed metal channels, but does not wet the bitartrate rows, which appear hydrophobic, despite the available OH group.…”
Section: Introductionmentioning
confidence: 88%
“…23,24 Steric effects in lateral interactions between adsorbed molecules are responsible for the segregation of different enantiomers of a racemic mixture into 2D domains of opposite handedness, 25,26 but the interaction with the substrate can also provoke deformations of the molecules influencing their arrangement on the surface. 27 Fabricating spatially uniform chiral thin films with atomic-scale control of their handedness is not only relevant for applications; it is also important to reach a profound understanding of the interactions between the chiral building blocks and the mechanisms allowing transmission of their chirality to long-scale arrangements because the details of these structures can have a substantial influence on their enantioselectivity. 28 In the last decades surface spectroscopies and scanning probe microscopies have provided important insights on chiral 2D assembly which complemented with advances in theoretical modeling have delivered understanding into the balance of interactions that determine the system behavior.…”
Section: Introductionmentioning
confidence: 99%